P558 Sexual health, syndemics and assets among men who have sex with men: secondary analysis of multi-national surveys. (14th July 2019) - Mcdaid, Lisa; Flowers, Paul; Ferlatte, Olivier; Mcaloney-Kocaman, Kareena; Gilbert, Mark; Frankis, Jamie
Abstract : Background: Globally, gay, bisexual and other men who have sex with men (GBMSM) experience an increased burden of poor sexual, mental and physical health. Syndemics theory provides a framework to understand these interrelated health problems and how to intervene. Methods: Comparative quantitative secondary analysis of syndemic-related data are presented from two international, online, cross-sectional surveys: SMMASH2 in Scotland, Wales, Northern Ireland and the Republic of Ireland (N=3220); and Sex Now in Canada (N=7872). Results: In both studies negative sexual, mental and physical health outcomes were clustered, providing evidence of the syndemic (SMMASH2 O/E Ratio=1.32, 95% CI 1.25–1.40; Sex Now O/E Ratio=1.59, 95% CI 1.45–1.73). There were differences between the studies in the variables that were associated with experience of the syndemic. In Sex Now we found experience of the syndemic was associated with worries about sexuality-related stigma (AOR 1.87, 95% CI 1.23–1.54) and experience of discrimination (AOR=1.83, 95% CI 1.60–2.10). Equally, some community assets appeared to have a protective effect on the experience of syndemics. In Sex Now, aspirations were significant; e.g., being unlikely to achieve quality of life significantly associated with increased odds of experiencing the syndemic (AOR=1.89, 95% CI 1.63–2.19), while measures of community engagement were not significant. In SMMASH2, sense of coherence – a measure of resilience – was significant (AOR=0.98, 95% CI 0.96–0.99), indicating that higher sense of coherence was associated with decreased odds of experiencing the syndemic. Conclusion: These results present an important step forward in our understanding of syndemics. They provide new insights into how to intervene to reduce the interrelated burden of poor sexual, mental and physical health among GBMSM and point to a theoretical mechanism through which assets-based approaches to health improvement could function. Disclosure: No significant relationships.